Full flexible performance characterization of a feedback applied transistor with LNA applications - Gunes, Filiz; Yurttakal, Oktay (WILEY, 2020)
In this paper, the full flexible performance characterization of a transistor with series inductive/parallel capacitive feedback is carried out in terms of LNA applications. For this purpose, the input VSWR V-in-maximum available gain G(Tmax) variations are constructed for a high technology low-noise transistor that is subject to the required noise figure F-req(f) >= F-min(f) along the device's operation band depending on the feedback. These V-in-G(Tmax) variations result in the application of a design chart that indicates which value of feedback can be applied within which region of the operation band with the improvable trade-off between the V-in and output VSWR V-out for the F-req(f) >= F-min(f). Following this, the optimum trade-off between V-in and V-out is made for the necessary operation frequency regions using the load impedance Z(L) as an instrument with the predetermined source impedance Z(S). Finally, the LNA applications of a series inductive/parallel capacitive feedback applied transistor with the optimum V-in, V-out, and G(T) subject to F-req(f) >= F-min(f) are also presented as distributed across the entire bandwidth in the different operation bands. It can be concluded that this rigorous work will enable a designer to utilize the entire operation frequency band of transistor through using only a single series inductive/parallel capacitive feedback for the LNA designs of F-req(f) >= F-min(f) with the optimum trade-offs among its performance measures.
Keywords: feedback; gain; microwave transistor; noise figure; stability; VSWR; NOISE; SIGNAL; DESIGN; MODEL; Engineering